2022
DOI: 10.3390/medicina58030338
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anticoagulant Therapy in Patients with Acute Myocardial Infarction and Atrial Fibrillation

Abstract: The incidence of atrial fibrillation (AF) in acute coronary syndrome (ACS) ranges from 2.3–23%. This difference in the incidence of AF is explained by the different ages of the patients in different studies and the different times of application of both reperfusion and drug therapies in acute myocardial infarction (AMI). About 6–8% of patients who underwent percutaneous intervention within AMI have an indication for oral anticoagulant therapy with vitamin K antagonists or new oral anticoagulants (NOAC).The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…However, the received changes in ATT prescription for patients with AF and MI at that time, especially the increase in TATT prescription, should be regarded positively as a result of a long and gradual implementation of the ongoing clinical recommendations at that time (2016), in which is stated that “in patients with AF and atrial flutter at risk of stroke and acute coronary syndrome undergoing PCI, TATT is recommended to be extended up to 6 months after PCI” [ 4 ]. In the same recommendations, it is indicated that a high risk of bleeding is compared with the risk of recurrent acute coronary syndrome or stent thrombosis, and it is possible to reduce the duration of TATT to 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the received changes in ATT prescription for patients with AF and MI at that time, especially the increase in TATT prescription, should be regarded positively as a result of a long and gradual implementation of the ongoing clinical recommendations at that time (2016), in which is stated that “in patients with AF and atrial flutter at risk of stroke and acute coronary syndrome undergoing PCI, TATT is recommended to be extended up to 6 months after PCI” [ 4 ]. In the same recommendations, it is indicated that a high risk of bleeding is compared with the risk of recurrent acute coronary syndrome or stent thrombosis, and it is possible to reduce the duration of TATT to 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…In the same recommendations, it is indicated that a high risk of bleeding is compared with the risk of recurrent acute coronary syndrome or stent thrombosis, and it is possible to reduce the duration of TATT to 1 month. Dual therapy of OAC with aspirin or clopidogrel may be considered in certain cases, especially for patients who have not undergone stenting [ 4 ]. A similar fact of gradual implementation of clinical recommendations is shown in other works [ 27 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation